Augmentation of freshwater productivity in single slope solar still using Luffa acutangula fibres - Subbarama Kousik Suraparaju (IWA Publishing, 2021)
The prime intention of the current research is to enhance the freshwater productivity of the solar still (SS) by using Luffa acutangula fibres (LAF). The dried LA fibres were introduced into the absorber basin of a solar still to enhance the wet surface area through its porous structure that leads to augmented evaporation of water from the absorber basin. The effect of the number of LAF in the absorber basin such as 10,13,14,15,16,20 and 25 on freshwater productivity was estimated. The results revealed that SSLAF with 15 fibres in the absorber basin increased the yield by 25.23%. Besides, a solar still with 10,13,14,16,20 and 25 fibres in the absorber basin increased the yield by 12.27%, 17.45%, 22.04%, 22.69%, 14.64% and 4.09% respectively when compared to conventional solar still (CSS). The average thermal efficiency of the SSLAF with 15 LAF was increased by 28.35% whereas, for 10,13,14,16,20 and 25 LAF, the average thermal efficiency was increasedby 11.05%, 16.99%, 22.53%, 19.93%, 11.29% and 3.9% respectively when compared to CSS.The economic analysis resulted that the cost per litre freshwater yield from the SSLAF is 22.5% lower than CSS. Also, the payback period of SSLAF is comparatively lesser than that of CSS. HIGHLIGHTS This study analysed the thermal and economic performance of SSLAF.; The optimum number of fibres in the basin is observed as 15.; The productivity of solar still with 15 LAF is increased by 25.23%.; The energy efficiency of solar still with 15 LAF is increased by 28.35%.; Economic analysis showed that the CPL of SSLAF is 22.5% less than that of CSS.;